Website Quality and User Satisfaction: Evidence from Tokopedia Users in Mataram - Rizal Ramdani; Arwin Yafi Rahmatullah; Stevany Hanalyna Dethan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of website quality dimensions: usability quality and interaction quality on Tokopedia user satisfaction in Mataram. This research employed a quantitative descriptive approach using multiple linear regression analysis. The sample consisted of 110 respondents selected through purposive sampling in Mataram who actively use Tokopedia. Data were collected through a structured questionnaire using a Likert scale. The findings indicate that usability quality has a positive and significant effect on user satisfaction. Interaction quality also demonstrates a positive and significant effect on user satisfaction. Thus, both independent variables significantly influence user satisfaction. The coefficient of determination (R²) is 0.621, suggesting that 62.1% of the variance in user satisfaction is explained by usability quality and interaction quality. These findings highlight the importance of enhancing website quality dimensions as a user-centered strategy for improving digital business performance. Therefore, this study contributes to the growing literature on e-commerce service quality by providing empirical evidence from emerging urban consumers and offers practical insights for digital platform managers to strengthen customer retention, improve user experience, and maintain competitive advantage in the rapidly evolving online marketplace. Furthermore, the results provide valuable guidance for developing more effective digital service strategies that align with evolving consumer expectations.